THE MISCIGENATION AS THE NEGATION OF THE OTHER: THE INDIOS ALDEADOS AND THE END OF THE ALDEAMENTOS PAULISTAS - Berpateli, Vladimir [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias Humanas & Sociais, 2017)
This paper aims to discuss the process of negation, or deletion, who underwent the so called indios mansos living in the settlements allocated in the province of Sao Paulo in the second half of the nineteenth century. Demonstrate that such deletion was grounded on miscegenation such population with the Indians not inhabiting the adjacent land, causing those were considered assimilated or seen not as Indians. We will see how this argument was widely used by administrators, politicians and settlers to expropriate the land of such groups of indigenous concentration. Therefore, based on an interdisciplinary approach between History and Anthropology, I try to analyze the primary documentation - letters and reports - and the research conducted so far on the subject in question.
Keywords: Miscigenation; Indigenous; Aldeamentos; Lands